Ambulatory care of patients with pancreatic diabetes: experienceof application of hospital-substituting technologies - Ye. B. Kravets; A. T. Adamyan; I. S. Zubrilin; T. U. Koschevets; O. Yadmaa; A. N. Astafurov (Бюллетень сибирской медицины, 2008)
Under conditions of epidemic of pancreatic diabetes (PD), it is necessary to enhance the prehospital stage of diabetological care. Capabilities of hospital-substituting technologies are used insufficiently in endocrinology now. Organization of a day endocrinological hospital based on the Tomsk Municipal Hospital No. 3 was an attempt to apply hospital-substituting forms at the municipal level. In this day hospital, 260 patients with Type 1 and 2 pancreatic diabetes have been treated. The cost for treatment of one patient in the day hospital was 3.16 times lower than that in a twenty-four hour hospital. Patients of the day endocrinological hospital have achieved the target values of postprandial glycemia. With proper organization of the prehospital stage of diabetic care, it is possible to achieve medical targets of treatment of Type 1 and 2 PD.